Keterkaitan Pengelolaan Keuangan dan Kapabilitas Sumber Daya Manusia Terhadap Efektivitas Penggunaan Anggaran Daerah - Nabilah Hafizhah; Diah Retno Dwi Hastuti; Sri Astuty; Citra Ayni Kamaruddin; Abdul Rajab (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to identify the relationship between budget planning and human resource competencies on budget absorption rates, as well as to analyze the effectiveness of these two aspects at the Makassar City Regional Development Planning Agency for the 2020–2024 period. The data used consisted of budget realization reports and personnel data, which were then analyzed using Spearman’s rank correlation to examine the relationships among the variables. The results of the study indicate that budget planning has a positive relationship with budget absorption rates, with a correlation coefficient of 0.583, which falls into the moderate category. Meanwhile, human resource competency exhibits a very strong positive relationship, with a correlation coefficient of 0.955. These findings indicate that while budget planning plays a role in improving budget absorption, human resource competency has a more dominant influence in supporting the effectiveness of budget implementation. Therefore, improving the quality of human resources as well as enhancing coordination and the implementation of planning are strategic steps in optimizing budget absorption.